Estrogen variation during the menstrual cycle does not influence left ventricular diastolic function and untwisting rate in premenopausal women. Issue 1 (January 2017) - Hirose, Kuniaki; Daimon, Masao; Miyazaki, Sakiko; Chiang, Shuo-Ju; Morimoto-Ichikawa, Ryoko; Maruyama, Masaki; Kawata, Takayuki; Ohmura, Hirotoshi; Daida, Hiroyuki
Abstract: Background: Although a cardioprotective effect of estrogen has been suggested by experimental studies, clinical data on the influence of estrogen on left ventricular (LV) diastolic function are sparse. The LV untwisting rate obtained by 2D speckle tracking echocardiography (2D-STE) is correlated with the time constant of LV pressure decay (tau), and this correlation is independent of left atrial pressure. Therefore, we used conventional Doppler echocardiography and 2D-STE to investigate changes in LV diastolic function during a single menstrual cycle in premenopausal women. Methods: Twenty healthy premenopausal woman (mean age, 28.1 ± 2.7 years) were enrolled. Clinical and echocardiographic data were obtained during the follicular phase (F-phase) and luteal phase (L-phase) of a single menstrual cycle. We compared the clinical and echocardiographic data, and estrogen levels between the two phases. Results: There were no significant differences in LV diastolic parameters derived from Doppler echocardiography ( E / A, p = 0.295; E / e ′, p = 0.449, DcT, p = 0.178) or 2D-STE (peak untwisting rate, p = 0.892; time-to-peak untwisting, p = 0.951) between the two phases of the menstrual cycle. However, there was a significant decrease in estrogen levels between the F- and L-phases (177 ± 119 pg/ml vs. 35 ± 12 pg/ml, p < 0.0001). Conclusions: LV diastolic function in healthy premenopausal women did not significantly change during the menstrual cycle. Estrogen does not appear to have a significant acute effect on LV diastolic function in premenopausal woman.